DIGITAL LEADERSHIP AND CREATIVE PERFORMANCE IN TOURISM AND HOTEL ENTERPRISES: LEVERAGING STRATEGIC AGILITY AND ORGANIZATIONAL LEARNING CULTURE - Tarik Ali JASIM; Hazem Ahmed KHAIRY; Sameh FAYYAD; Bassam Samir AL-ROMEEDY (Geo Journal of Tourism and Geosites, 2024)
The aim of this study is to explore the effect of digital leadership (DL) on creative performance (CP) by investigating the mediating roles of strategic agility (SA) and organizational learning culture (OLC) in tourism and hospitality industry. The study analyzed 320 responses from middle-level management at five-star hotels and category-A travel agencies in Egypt using the PLS-SEM technique and WarpPLS statistical software 7.0. Findings reveal that digital leadership positively affects creative performance, strategic agility, and organizational learning culture. In addition, CP is positively affected by SA and OLC. Moreover, findings confirm the mediation effects of strategic agility and organizational learning culture in the DL→CP relationship. The study provides practical insights for tourism and hospitality enterprises using Dynamic Capabilities Theory to enhance performance and agility in the digital age.